Approximation length of the mandibular first molar tooth of Bataknese based on gender analyzed using parallel techniques - Manja, Cek Dara; Salam, Ummu Mahfuzah Nur (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: The purpose of this study is to use the parallel technique to approximate the tooth, root, and furcation length of the mandibular first molar in the Bataknese population while accounting for gender differences. Materials and Methods: The research employs an analytic observational design with a cross-sectional approach. It utilizes secondary data from 90 parallel technique radiographs of patients aged 19-25 years who meet the specific inclusion and exclusion criteria. The radiographs are analyzed to assess tooth length, roots, and furcation of the mandibular first molar. Measurements are conducted using Cliniview software, and the results are processed and analyzed utilizing an independent t-test. Results: The result showed that the average tooth length in males was 21.60 mm, with the mesial root measuring 13.64 mm, the distal root measuring 12.78 mm, and the furcation measuring 4.25 mm. In females, the average tooth length was 19.50 mm, with the mesial root measuring 12.13 mm, the distal root measuring 11.24 mm, and the furcation measuring 3.56 mm. Males have a greater average length than females. Conclusion: Male teeth, roots, and furcations are longer than female teeth, according to the study's findings, which were derived via an analysis using the parallel technique. There was a discernible gender difference.